"But they told me it was professional": Extrinsic factors in the evaluation of musical performance. (January 2017) - Kroger, Carolyn; Margulis, Elizabeth Hellmuth
This study investigated the performance preferences of listeners without formal training in music. Specifically, it asked whether the quality of the performance (as represented by the status of the performer), the order of presentation of the performances, and extrinsic information about the quality of the performance impacted preferences. In Experiment 1, participants heard pairs of performances of solo piano music and were informed that one was played by a conservatory student, and one by a world-renowned professional. After each pair, they selected the one they thought had been performed by the professional. Their responses seem to have been driven by a combination of a preference for the performance actually played by the professional and a preference for the second performance in the pair. In Experiment 2, they heard the same performance pairs, but this time were informed, correctly or incorrectly, before each performance whether it was played by a student or by a professional. After each pair, they selected the performance they preferred. This time, their responses were influenced not just by the actual performer identity and the order of presentation, but also by the priming condition. Listener preferences seem to be driven by a combination of factors intrinsic and extrinsic to the performance itself.